Competency Evaluation of Electrical Installation Field Practice of Vocational High School Students in Manado - Ponto, Rudy Sanger; Hantje (International Journal of Psychosocial Rehabilitation, 2020)
Evaluation is an integral part of education process. Field practice competency of vocational high school students needs to be evaluated in order to know their learning development and outcome. Result of the evaluation can be a reference to the improvement of learning activity implementation including the used methods. This research aimed to find out students’ learning development and outcome regarding to the Electrical Installation subject of VHS in Manado, North Sulawesi Province, Indonesia. Research method was survey method. Research data was qualitatively analyzed. Research finding showed that students’ competency in Electrical Installation subject was categorized high..